A Comparison of Unconventional Microwave and Ultrasound-Assisted Extraction Methods used for Flavonoids - Rahmawati, Istiqomah; Azizi, Daffa Hafiziaulhaq; Wibowo, Jihan Nafila; Reza, Muhammad; Fachri, Boy Arief; Palupi, Bekti; Rizkiana, Meta Fitri; Amini, Helda Wika; Ramadana, Ifan; Setiawan, Felix Arie (Makara Journal of Science, 2025)
Cocoa pods (Theobroma cacao L.) are a rich source of flavonoids, which are natural antioxidants known for their health benefits. This study investigated the use of microwave-assisted extraction (MAE) and ultrasound-assisted ex-traction (UAE) to extract the maximum flavonoids and antioxidants from cocoa pods. MAE and UAE are efficient and sustainable methods for extracting bioactive compounds like flavonoids and antioxidants from cocoa pods, offer-ing faster extraction, reduced solvent use, and better compound preservation compared to conventional methods. These technologies unlock the untapped potential of cocoa pods for applications in food, cosmetics, and pharmaceuti-cals. The effects of extraction time (2–10 min), microwave power (100–300 W), and the ratio of cocoa husk powder to solvent (0.02–0.06 g/mL) were evaluated for MAE. Meanwhile, for UAE, different temperatures (30–50 °C), times (10–30 min), and powers (16–48 W) were studied. The Design-Expert® software with Response Surface Methodology (RSM) and a Box-Behnken Design was utilized to analyze the effects of a combination of these parameters. The re-sults showed that extraction time, microwave power, and the ratio of cocoa husk powder–solvent significantly affected the total flavonoid yield and antioxidant capacity. The highest total flavonoid yield obtained by the MAE method (123.07 ppm) was at an extraction time of 10 min, cocoa husk–solvent ratio of 0.06 mg/mL, and microwave power of 300 W. The extract obtained by the MAE method showed an excellent antioxidant capacity of 43.49 mg/mL GAEAC, and a robust antioxidant activity indicated by an IC50 value of 42.19. Conversely, the highest total flavonoid yield of the UAE method (8.45 mg/mL GAEAC) was achieved at 30 min, 40 °C, and 40 W. The extract from the UAE method demonstrated a better antioxidant capacity (7.51 mg/mL GAEAC) and antioxidant activity (IC50 value of 23.46) than that from the MAE technique